Relationship Between the Urine Flow Rate and Risk of Contrast-Induced Nephropathy After Emergent Percutaneous Coronary Intervention. Issue 50 (December 2015) - Liu, Yong; Lin, Lixia; Li, Yun; Li, Hualong; Wu, Deng-Xuan; Zhao, Jian-bin; Lian, Dan; Zhou, Yingling; Liu, Yuanhui; Ye, Piao; Ran, Peng; Duan, Chongyang; et al.
Abstract : Abstract: A low urine flow rate is a marker of acute kidney injury. However, it is unclear whether a high urine flow rate is associated with a reduced risk of contrast-induced nephropathy (CIN) in high-risk patients. We conducted this study to evaluate the predictive value of the urine flow rate for the risk of CIN following emergent percutaneous coronary intervention (PCI). We prospectively examined 308 patients undergoing emergent PCI who provided consent. The predictive value of the 24-hour postprocedural urine flow rate, adjusted by weight (UR/W, mL/kg/h) and divided into quartiles, for the risk of CIN was assessed using multivariate logistic regression analysis. The cumulative incidence of CIN was 24.4%. In particular, CIN was observed in 29.5%, 19.5%, 16.7%, and 32.0% of cases in the UR/W quartile (Q)-1 (≤0.94 mL/kg/h), Q2 (0.94–1.30 mL/kg/h), Q3 (1.30–1.71 mL/kg/h), and Q4 (≥1.71 mL/kg/h), respectively. Moreover, in-hospital death was noted in 7.7%, 3.9%, 5.1%, and 5.3% of patients in Q1, Q2, Q3, and Q4, respectively. After adjusting for potential confounding predictors, multivariate analysis indicated that compared with the moderate urine flow rate quartiles (Q2 + Q3), a high urine flow rate (Q4) (odds ratio [OR], 2.69; 95% confidence interval [CI], 1.27–5.68; P  = 0.010) and low urine flow rate (Q1) (OR, 2.23; 95% CI, 1.03–4.82; P  = 0.041) were significantly associated with an increased risk of CIN. Moreover, a moderate urine flow rate (0.94–1.71 mL/kg/h) was significantly associated with a decreased risk of mortality. Our data suggest that higher and lower urine flow rates were significantly associated with an increased risk of CIN after emergent PCI, and a moderate urine flow rate (0.94–1.71 mL/kg/h) may be associated with a decreased risk of CIN with a good long-term prognosis after emergent PCI.